A qualitative inquiry into the capital structure decisions of overconfident finance managers of family-owned businesses in India. (2nd September 2021) - Mundi, Hardeep Singh; Kaur, Parmjit; Murty, R.L.N.
Abstract : Purpose: The purpose of this study is to understand the impact of the overconfidence of finance managers on the capital structure decisions of family-run businesses in the Indian scenario. Furthermore, this study aims to demonstrate that measurable managerial characteristics explain the capital structure decisions of managers. Design/methodology/approach: The qualitative approach to research, which aims at understanding a given phenomenon among the experts, is followed. Semi-structured interviews are conducted with 21 overconfident finance managers of family-owned businesses. Content analysis is used to analyse the collected data regarding capital structure decisions into several themes to fully explore the issue in the Indian scenario. Findings: In terms of preference for cash or debt, most of the responding overconfident finance managers of family-run businesses agreed that cash is the preferred source of financing over debt financing. This is due to the biased behaviour of overconfident managers, who consider lower availability of debt as a reason to prefer cash over debt financing. The present study reports that overconfident finance managers prefer short- to long-term debt financing. These managers raise certain practical issues, such as stringent debt terms and inflexible repayment schedules, that arise in relation to the long-term debt market. The study also finds that overconfident finance managers do not fully use tax savings. Respondents reported a lack of access to the debt market and a lack of expertise in capital structure decisions as factors in these capital structure decisions. In addition, the study explores various factors, such as the role of government, the Central Bank of India and industry practices, in relation to capital structure decisions. The study finds that the capital structure decisions of these overconfident finance managers are suboptimal because of the presence of overconfidence bias. Research limitations/implications: This study gathers information from respondents who are finance managers, not top-level managers, of family businesses; the decision not to interview the higher-ranking managers is a potential limitation of the present study. Another limitation is the small number of respondents in a specific firm size. Because of these factors, the generalisability of the findings of this study will obviously be restricted. Practical implications: The present study has several practical implications. The first is the recognition of overconfidence bias as it affects the decision-making of finance managers. Executives, especially finance executives, will benefit from the recognition of overconfidence bias and will understand how the presence of such bias impacts corporate decision-making. Managers will understand that bias leads to faulty decision-making. The study will provide indirect feedback to policymakers and regulators in terms of understanding the role of macroeconomic variables in economic decisions. The qualitative approach followed in the present study may enhance the understanding of capital structure decisions from a psychological perspective. The majority of studies in the review of literature adopt quantitative approaches; so the qualitative approach adopted here represents a methodological innovation, and it may provide a deeper understanding of the matter. Originality/value: The existing literature includes quantitative research aimed at understanding the impact of CEO overconfidence on various corporate policies such as capital budgeting, mergers and acquisitions, dividend policy and capital structure decisions. Quantitative research into the presence of overconfidence bias among executives and its impact on corporate policies returns mixed results. To fulfil the need for studies of overconfidence bias among executives with practical implications, this study explores the presence of overconfidence bias among finance managers in family-run businesses and investigates the impact of overconfidence on capital structure decisions.